Rheological and local fluid dynamics in foams - Craus, Maria Dolores Alonso (Trinity College (Dublin, Ireland). School of Physics, 2005)
This thesis explores the physics of foams, particularly those that are wet (i.e. have a high liquid fraction). The properties which are measured here relate to structure, drainage and rheology. We have performed the first published Stokes experiment in a foam [41 ]. and compared results with estimates derived from the Herschel-Bulkley model for rheology. The first extensive, systematic experiments on drainage driven instabilities reveal aspects hitherto unreported, including hysteresis and the existence of a cylindrically symmetric case. We offer a preliminary theoretical analysis of the case in w hich the column is tilted. Other new results relate to the structure of finite 2D clusters [93].
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin